Modified Duo Tir as an Alternative Training Media to Improve Shooting Accuracy in Petanque - Muhammad Ridwan Lubis; Andi Gilang Permadi; Isyani Isyani (Journal of Innovation in Educational and Cultural Research, 2023)
Le Duo TirObut is a training medium to improve the accuracy of shooting petanque. The price of these tools is relatively expensive and to get them must be imported. This study aims to: (1) produce a tool, namely Duo Tir which is modified with the materials used are relatively cheap and easy to obtain, this tool as an alternative training medium to improve shooting accuracy, and (2) determine the effectiveness of using a modified Duo Tir for increase the accuracy of shooting petanque. This study uses research and development methods by Borg and Gall. Data collection in this study implemented 6 data collection activities using 4 main instruments, namely observation, questionnaires, interviews, and shooting accuracy tests. The results of this study are: (1) the modified Duo Tir instrument to improve the accuracy of shooting petanque both from the content and construct aspects is valid and reliable, (2) the validator's assessment of the modified Duo Tir product, the results of preliminary field testing and main field testing with the percentage of eligibility 75% is feasible, and (3) the results of the effectiveness test show that training using a modified Duo Tir has a greater effect than conventional training on the results of increasing the accuracy of shooting for petanque athletes in NTB. Based on this explanation, it is concluded that the modified Duo Tir is feasible and effective to use to increase the accuracy of shooting petanque